Bone Mineral Density and Risk of Heart Failure in Older Adults: The Cardiovascular Health Study. Issue 3 (13th March 2017) - Fohtung, Raymond B.; Brown, David L.; Koh, William J. H.; Bartz, Traci M.; Carbone, Laura D.; Civitelli, Roberto; Stein, Phyllis K.; Chaves, Paulo H. M.; Kestenbaum, Bryan R.; Kizer, Jorge R.
Abstract : Background: Despite increasing evidence of a common link between bone and heart health, the relationship between bone mineral density (BMD) and heart failure (HF) risk remains insufficiently studied. Methods and Results: We investigated whether BMD measured by dual‐energy x‐ray absorptiometry was associated with incident HF in an older cohort. Cox models were stratified by sex and interactions of BMD with race assessed. BMD was examined at the total hip and femoral neck separately, both continuously and by World Health Organization categories. Of 1250 participants, 442 (55% women) developed HF during the median follow‐up of 10.5 years. In both black and nonblack women, neither total hip nor femoral neck BMD was significantly associated with HF; there was no significant interaction by race. In black and nonblack men, total hip, but not femoral neck, BMD was significantly associated with HF, with evidence of an interaction by race. In nonblack men, lower total hip BMD was associated with higher HF risk (hazard ratio, 1.13 [95% CI, 1.01–1.26] per 0.1 g/cm 2 decrement), whereas in black men, lower total hip BMD was associated with lower HF risk (hazard ratio, 0.74 [95% CI, 0.59–0.94]). There were no black men with total hip osteoporosis. Among nonblack men, total hip osteoporosis was associated with higher HF risk (hazard ratio, 2.83 [95% CI, 1.39–5.74]) compared with normal BMD. Conclusions: Among older adults, lower total hip BMD was associated with higher HF risk in nonblack men but lower risk in black men, with no evidence of an association in women. Further research is needed to replicate these findings and to study potential underlying pathways.